2021
DOI: 10.1016/j.idcr.2021.e01200
|View full text |Cite
|
Sign up to set email alerts
|

Native valve endocarditis and pacemaker infection with Mycobacterium fortuitum

Abstract: Endocarditis and cardiac device infection due to Mycobacterium fortuitum is a rare entity in the hospital settings. We report a case of pacemaker infection and native valve endocarditis due to Mycobacterium fortuitum , which was associated with tricuspid valve vegetation. two days after admission with fever, chills, body aches and swelling around her pacemaker, the patient’s pacing system was surgically removed. The patient was then discharged at day 16 after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The duration of antimicrobial therapy for CIED infections depends on the extent of infection, the presence of bloodstream infection, and type of causative organism [33] . M. fortuitum is the most common RGM that has been implicated in CIED infections in previous case reports [11] , [12] , [28] , [30] . Cure of the infection and successful reimplantation have been described in previous cases with complete device removal and appropriate antimicrobial therapy; duration of antimicrobial treatment was quite varied, from four weeks to six months in cases without valvular involvement or bacteremia [12] , [28] , [30] .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The duration of antimicrobial therapy for CIED infections depends on the extent of infection, the presence of bloodstream infection, and type of causative organism [33] . M. fortuitum is the most common RGM that has been implicated in CIED infections in previous case reports [11] , [12] , [28] , [30] . Cure of the infection and successful reimplantation have been described in previous cases with complete device removal and appropriate antimicrobial therapy; duration of antimicrobial treatment was quite varied, from four weeks to six months in cases without valvular involvement or bacteremia [12] , [28] , [30] .…”
Section: Discussionmentioning
confidence: 92%
“…M. fortuitum is the most common RGM that has been implicated in CIED infections in previous case reports [11] , [12] , [28] , [30] . Cure of the infection and successful reimplantation have been described in previous cases with complete device removal and appropriate antimicrobial therapy; duration of antimicrobial treatment was quite varied, from four weeks to six months in cases without valvular involvement or bacteremia [12] , [28] , [30] . Interestingly, none of the patients in our series demonstrated cardiac valvular infection with RGM.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, a patient with a history of mitral valve replacement eight years prior was diagnosed with M.fortuitum pulmonic valve endocarditis [44]. Another patient with a surgical history of cardioverter-defibrillator implantation was diagnosed with native valve endocarditis and M.fortuitum pacemaker infection [45]. A Serbian study found that three children received combination treatment for M. fortuitum-related endocarditis shortly after cardiac surgery [46].…”
Section: Atypical Mycobacteria Endocarditismentioning
confidence: 99%